2020
DOI: 10.1038/s41598-020-66847-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate aberrantly methylated and differentially expressed genes in Esophageal squamous cell carcinoma

Abstract: Aberrant methylated genes (DMGs) play an important role in the etiology and pathogenesis of esophageal squamous cell carcinoma (ESCC). In this study, we aimed to integrate three cohorts profile datasets to ascertain aberrant methylated-differentially expressed genes and pathways associated with ESCC by comprehensive bioinformatics analysis. We downloaded data of gene expression microarrays (GSE20347, GSE38129) and gene methylation microarrays (GSE52826) from the Gene Expression Omnibus (GEO) database. Aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…As a member of LETM1-binding genes, kinesin family member 14 (KIF14), a potential oncogene, exhibited promotive effects on the malignant development of many cancers, including gastric cancer [8], colorectal cancer [9] and glioma [10]. Previous studies have verified that KIF14 was overexpressed in ESCC [11,12]. Therefore, it is meaningful to investigate LETM1 and KIF14 together.…”
Section: Introductionmentioning
confidence: 99%
“…As a member of LETM1-binding genes, kinesin family member 14 (KIF14), a potential oncogene, exhibited promotive effects on the malignant development of many cancers, including gastric cancer [8], colorectal cancer [9] and glioma [10]. Previous studies have verified that KIF14 was overexpressed in ESCC [11,12]. Therefore, it is meaningful to investigate LETM1 and KIF14 together.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all aforementioned cell cycle markers are involved in tumorigenesis ( 32 - 36 ). Additionally, abnormal expression of KIF14 is often accompanied by abnormal expression of BUB1, TTK, PLK1, CREBBP, and CDK1 and affects the prognosis of several types of cancer (e.g., esophageal squamous cell carcinoma, glioblastoma, retinoblastoma, multiple myeloma, and acute myeloid leukemia) ( 37 - 39 ). Chen et al ( 40 ) found the overexpressed genes (BUB1, BUB1B, TTK, and KIF14) in gastric cancer, which are important parameters included in the nomogram to predict the probability of relapse for gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of desmosome proteins will promote the process of epithelial-mesenchymal transition (EMT) 22 . As a member of this family, the decreased expression of DSG1 has been reported to be closely related to the occurrence of tumors and poor prognosis in a variety of tumors, including lung cancer, esophageal squamous cell carcinoma, extrahepatic cholangiocarcinoma, anal carcinoma, etc [22][23][24][25] . The studies in OSCC also suggested that the abnormal decrease of DSG1 leads to the loss of intercellular connectivity, thus promoting tumor progression 26,27 .…”
Section: Discussionmentioning
confidence: 99%